2020
DOI: 10.33215/sjom.v3i2.292
|View full text |Cite
|
Sign up to set email alerts
|

Audit Committee Effectiveness and Earnings Management Among Publicly Listed Firms in Kenya

Abstract: Objective: The paper sought to investigate the role of an effective audit committee in controlling earnings management practices. Design / Methodology: A panel data sourced from the audited financial reports of firms listed at the Kenyan Nairobi Securities Exchange for the periods between 2004 and 2017 were analyzed using a panel regression model. Findings: Audit committee effectiveness proved an important monitoring mechanism for earnings management. The independence, Meeting frequency, and financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…Thus, UAE companies enhance the requirement of audit committee expertise and improve its role to detect management misbehaviour. This result is in line with Juhmani (2017) and Kapkiyai et al (2020) who found that audit committee expertise is negatively associated with earnings management.…”
Section: Multiple Regression Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Thus, UAE companies enhance the requirement of audit committee expertise and improve its role to detect management misbehaviour. This result is in line with Juhmani (2017) and Kapkiyai et al (2020) who found that audit committee expertise is negatively associated with earnings management.…”
Section: Multiple Regression Resultssupporting
confidence: 89%
“…Zábojníková (2016) and Deslandes et al (2020) reported that an audit committee's number of meetings is positively associated with firm performance. Kapkiyai et al (2020) reported that a high level of audit committee meetings indicates a high level of activeness against managers' misconduct. According to the Corporate Governance code of UAE, an audit committee should meet at least 4 times a year.…”
Section: Audit Committee Meetingsmentioning
confidence: 99%
See 3 more Smart Citations